Personal predictors of loneliness in adolescents - Ksionda, Olga G.; Marchenko, Annа E. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The experience of loneliness in adolescence is one of the norms of age development. The system of values is rebuilt, a sense of adulthood appears, which gives rise to new experiences, including the experience of misunderstanding on the part of loved ones and, as a result, the experience of loneliness. Loneliness is a mental state of a person associated with the lack of close, positive emotional ties with people and or with the fear of losing them as a result of forced or psychologically caused social isolation, which is accompanied by a deep (often negatively coloured) emotional experience. Such personal predictors of experiencing loneliness in adolescence as character accentuation (distimism, cyclothymism, excitability) and personality traits (impulsivity and emotional instability) have been identified. The combination of these factors leads to a deeper experience of loneliness in adolescents.
Keywords: adolescence; the experience of loneliness; personal predictors of the experience of loneliness